Biological and Cultural Ecotourism Interpretation of Mekar Utama Village, Kendawangan District, West Kalimantan - Sarma Siahaan; Reine Suci Wulandari; Andre Sidabutar; Muflihati (Talenta Publisher, 2022)
Mekar Utama Village, located in the Ketapang Industrial Forest Area (Hutan Ketapang Industri-HKI), is a unique and attractive ecotourism site with various natural resources. This village's three hamlets have the potential for biological and cultural ecotourism. The study aims to obtain potential data and interpret the biological and socio-cultural ecotourism in Mekar Utama village. The method used was a survey with observation and interview approaches. Three interpretive tracks and 18 biological and cultural ecotourism potential were available at the study site. Nine potential plants found were kantung semar (Nepenthes sp. ), bamboo (Bambusa sp. ), bajakah (Spatholobus littoralis Hassk), pasak bumi (Eurycoma longifolia Jack), ulin (Eusideroxylon zwageri), meranti (Shorea smithiana), gaharu (Aquilaria malaccensis), ketatai (Antiaris toxicaria) and pulai (Alstonia scholaris). Ulin, meranti, and gaharu are protected species. Kura-kura hutan (Dogania suplana), owa kelawat (Hylobates albibarbis), and honey bee (Apis koschevnikovi and Trigona sp.) were three unique animal species. Six potential cultures were found, i.e. ethnic, traditions, traditional rituals, arts, special foods, historical/sacred places, and folklore/myths. All the potentials were found in three interpretation tracks, i.e., the Gantang river hamlet, which was 6.5 km long and took 26 minutes to reach, the Sukaria hamlet, which was 5.3 km long and took 21